Compliance with physical activity guidelines in rural, black South Africans in the Limpopo Province: an energy expenditure approach. Issue 8 (22nd March 2011) - Cook, Ian; Alberts, Marianne; Lambert, Estelle V
Abstract : Objective: The authors used an energy expenditure–based approach to determine the non-compliance and compliance with public health physical activity (PA) guidelines in rural, black South Africans. Methods: The authors analysed 7-day objectively measured PA data (NL-2000 pedometer) in 508 females and 267 males. Compliance was defined for the American College of Sports Medicine guideline (ACSM: ≥7.5 to <21 kcal/kg/week and ≥1.5 kcal/kg/day for ≥5 days/week) and the Institute of Medicine guideline (IOM: ≥21 kcal/kg/week and ≥3 kcal/kg/day for 7 days/week). Results: The age- and sex-adjusted prevalence for non-compliance, ACSM compliance and IOM compliance in the sample was 7.8%, 55.0% and 37.2%, respectively. Complying with IOM guidelines required substantially more ambulation (14 522 steps/day) than ACSM guidelines (10 837 steps/day) and non-compliance (6420 steps/day) (p<0.0001). Approximately 95% of IOM-compliant subjects and 51% of ACSM-compliant subjects achieved ≥10 000 steps/day on 4–7 days. Compliance with IOM or ACSM guideline was associated with an 87% (p<0.0001) and a 49% (p=0.0647) reduced risk of obesity, respectively. Partial and full IOM compliance was associated with a significantly reduced risk of obesity (OR=0.58 to 0.16, p<0.04). Conclusions: The 10 000 steps/day guideline concurs with the ACSM guideline, whereas IOM compliance required higher ambulation levels. Compared with ACSM compliance, IOM compliance was associated with a lower risk of obesity.